Exploring University Toilet Signage as a Visual Communication Tool Through a Social Semiotics Lens in Brunei Darussalam - Siti Nurfarina Hasriana; Lee Kok Yueh (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2024)
Primarily, the linguistic landscape acts as a foundation for analysing how social, cultural and political structures are reflected in public signs. While previous studies have mainly focused on the linguistic elements and the semiotic principles of visual signs, this research explores how Brunei universities’ toilet signages are analysed and interpreted through a social semiotics approach. By employing convenience, purposive and snowball sampling, the data collected were from seven local and seven international university students' semi-structured interviews and one focus group discussion, consisting of the local students only. This study employed a social semiotics approach by Halliday (1978) to analyse the visual findings and to guide the interview data analysis gathered. Three major themes emerged based on the findings, namely: 1) Interpretation and user experience, 2) Cultural encoding in signage, and 3) Cross-cultural interpretation gap. These findings revealed that university students’ cultural background and their familiarity influence their interpretation of the signage. Findings also emphasised the dominant use of English in the signage, which raises questions about Malay visibility and institutional preferences. This study implies that although visuals can be similar, their meaning is not fixed but is shaped by individuals’ cultural and social backgrounds. Although the findings correspond to existing literature, limitations include restricted access only to UTB and UBD signage, which influence the findings of the study. Besides, this study only explored university students from UTB and UBD, which excludes other potential public users and staff who might have a different interpretation of the signages. Hence, it is recommended for future research to explore how toilet signage is interpreted in other institutions and how different demographic groups interpret signage as a visual communication tool to expand the research area for more in-depth findings.